Pemanfaatan Ekstrak Daun Teh (Camellia sinensis L) Dari Perkebunan Kemuning Kab. Karang Anyar dalam Pembuatan Sabun Padat Transparan dan Uji Aktivitas Antibakteri pada Staphyloccocus aureus - Setiawan, Iwan; Saryati, Dwi; Astian, Astian (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
Kemuning’s plantations in Karang Anyar Regency are famous for their lush tea plantations and good quality. Tea leaves contain several substances including flavonoids, 30- 40% polyphenols, caffeine, essential oils and tannins. The famous tea leaf polyphenols are catechins. Catechins have properties as antidiarrheal, antibacterial, especially against Staphyloccocus aureus bacteria, which is one of the gram-positive bacteria that cause infections in the skin. Based on this, tea leaf extract can be used as a natural supplement in the manufacture of transparent soap products. In this study tea leaf extract became one of the components in making transparent soap by adding tea leaf extract to formula 1 (0%), formula 2 (1.5%), formula 3 (3%) and formula 4 (4, 5%). Then transparent soap preparations were tested for organoleptic and quality quality including moisture and vaporizing soap content, amount of fatty acids, free alkali content and levels of unbunned fractions and anti-bacterial activity against the growth of Staphyloccocus aureus bacteria. Based on the results of the study, it was found that transparent 4 solid soap with 4.5% tea leaf extract content had the darkest color of solid soap, evaporated water and substance content, free alkali content, fatty acid, acidity level (pH), unbonded fraction level and the highest foam stability. Formula 4 solid soap also has the best inhibitory power against the growth of Staphyloccocus aureus bacteria.